Effects of muscle action type with equal impulse of conditioning activity on postactivation potentiation - Bogdanis, G. C.; Tsoukos, A.; Veligekas, P.; Tsolakis, C.; Terzis, G. (The Journal of Strength and Conditioning Research, 2014)
This study investigated the effects of muscle action type during conditioning activity (half-squat) on subsequent vertical jump performance. Fourteen track and field athletes (relative half-squat of 2.3 ± 0.3 times their body weight) completed 4 main trials in a randomized and counterbalanced order 5-7 days apart: (a) concentric (CON) half-squats: 7.5 ± 1.2 repetitions against 90% of 1 repetition maximum (1RM), (b) eccentric (ECC) half-squats: 9.3 ± 1.5 repetitions against 70% of 1RM, and (c) 3 sets of 3-second maximal isometric (ISO) half-squats, (d) a control (CTRL) trial, where subjects rested for 10 minutes. The number of repetitions in CON and ECC was adjusted so that the impulse of the vertical ground reaction force was similar to ISO. Countermovement vertical jump (CMJ) performance was evaluated for 21 minutes after each main trial. Countermovement vertical jump performance in ISO was higher than CTRL from the second to the 10th minute of recovery, whereas CMJ performance in ECC was higher than CTRL from the sixth and 10th minute of recovery. Analysis of the peak individual responses revealed an increase in CMJ performance compared with baseline only in ISO (3.0 ± 1.2%; p = 0.045), whereas no significant increases were observed in ECC and CON. Peak CMJ performance for all subjects in ISO and ECC was achieved within 2-10 minutes after the conditioning muscle actions. Isometric were more effective than CON and ECC muscle actions in increasing explosive leg performance when the impulse of the ground reaction force of the conditioning exercise was equated.